Policy responses and international migration to Britain since 1945 - Penn, Roger Penn; Perret, Joanna Perret; Lambert, Paul (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
The paper assesses policy responses to international migration into Britain since 1945. The immediate post-war period was characterized by accelerating immigration into Britain from the Caribbean, the Indian sub-continent and elsewhere from the former British Empire. Most international migrants arrived with British citizenship at that time and there were few specific policy responses to such immigration. The 1960s witnessed the beginning of the development of the ‘dual strategy’ to deal with the increasing ethnic heterogeneity of Britain. Successive Governments have progressively limited the right of access to Britain from the Commonwealth. This strategy has been labelled as «Fortress Britain» and has involved the racialization of entry requirements. Parallel to restrictions upon entry, policies have been developed across many areas of society to promote equal rights and opportunities for ethnic minorities. These include both first-generation international migrants and their descendants. Central to this policy has been legislation to outlaw racial discrimination. This has been championed by the national Commission for Racial Equality and local Community Race Councils. In the sphere of housing much policy impinges upon ethnic minorities. However, ethnic differences in housing tenure are deep-set within British society. Recently, the new Labour Government has put equal housing opportunities on the agenda once more. However, most implementation remains in the hands of voluntary associations and/or local agencies, and there is strong evidence that the deep structure of ethnic housing differences and disadvantage remains within contemporary Britain. In the sphere of education the picture is more complex and more diverse. Some ethnic minority groups achieve educational results well above the average for the autochthonous population. There are also significant gender differences between ethnic groups which continue to perplex sociologists.